Dynamical Analysis of Spherical Mobile Robot Utilizing Off-Centered Internal Mass Distribution. Issue 13 (2015) - Furuse, Y.; Hirano, T.; Ishikawa, M.
Abstract: Spherical rolling is an interesting methodology for locomotion from both nonlinear control and robotics points of view. In this paper, we propose a dynamical model of a spherical mobile robot with focus on the eccentricity of its center of gravity, i.e., the offset in the center of its mass distribution. The proposed robot has a rigid spherical shell as its body, which contains active 2-d.o.f. pendulum inside as the control component. The robot is supposed to roll on the at horizontal oor without any slippage, and to spin around the vertical axis depending on kinematical settings when allowed. Through the dynamical analysis based on the model and several numerical simulations, we observe that the settings concerned with the spin is so crucial that the sphere tends to be severely affected by the torque from the ground, and point out that it should be the essential factors for the modeling and new robot creation in the future work.